Financial Communication in Small and Medium-Sized Enterprises: Patents in Financial Communication - Zureck, Alexander (Springer, 2015)
To ensure refinancing opportunities for SMEs, answers for bridging the information gap between investor and company are needed; in this context, capital markets are becoming increasingly important. Alexander Zureck focuses on patents as an example of intangible assets and on their importance for the financial communication between SMEs and the capital market. A positive correlation between patent application and stock price development underscores the importance of patents. Based on his findings, the author recommends to take patents and other intangible assets into company's financial communication.